Rancang Bangun dan Analisa Media Video Streaming pada Jaringan 3G dan 4G - Andan Widya Kusuma (Politeknik Negeri Malang, 2018)
In this study, the authors built a website that can be used to stream video both realtime and On Demand using software specifically for streaming, namely DaCast and OBS Studio. The purpose of this livestreaming website is made because the video streaming system is broadcast, so we don't need to come to see something we want, because what is displayed is exactly the same as what was in the original, unless there are some video streaming problems, unless there are some problems such as in network performance or quality. This problem can be overcome by analyzing the quality of the network or what is called Quality Of Services (QoS) using the Wireshark application. QoS aims to help users be more productive by ensuring that users get reliable performance from network-based applications. The author analyzes the QoS of the website that has been made based on the parameters of Delay, Throughput and Packet Loss for 7 days, which are differentiated by working days and holidays, which are in the Malang State Polytechnic campus area with variations in the morning, afternoon and evening. Live Streaming test results on QoS parameters obtained are average delay on the 3G network is 119.6 ms and the 4G is 54.4 ms, the average throughput on the 3G network is 925 Kbps and 4G is 1496 Kbps, the average packet loss on 3G network is 11.3% ms and 4G is 27.27%